Short‐term physiological response to high‐frequency‐actuated pVAD support. Issue 12 (30th July 2019) - Rebholz, Mathias; Dual, Seraina; Batliner, Martin; Meboldt, Mirko; Schmid Daners, Marianne
Abstract: Ventricular assist devices (VADs) are an established treatment option for heart failure (HF). However, the devices are often plagued by material‐related hemocompatibility issues. In contrast to continuous flow VADs with high shear stresses, pulsatile VADs (pVADs) offer the potential for an endothelial cell coating that promises to prevent many adverse events caused by an insufficient hemocompatibility. However, their size and weight often precludes their intracorporeal implantation. A reduction of the pump body size and weight of the pump could be achieved by an increase in the stroke frequency while maintaining a similar cardiac output. We present a new pVAD system consisting of a pump and an actuator specifically designed for actuation frequencies of up to 240 bpm. In vitro and in vivo results of the short‐term reaction of the cardiovascular system show no significant changes in left ventricular and aortic pressure between actuation frequencies from 60 to 240 bpm. The aortic pulsatility increases when the actuation frequency is raised while the heart rate remains unaffected in vivo. These results lead us to the conclusion that the cardiovascular system tolerates short‐term increases of the pVAD stroke frequencies.